Characteristics and thermal cycling behavior of plasma-sprayed Ba(Mg1/3Ta2/3)O3 thermal barrier coatings. Issue 14 (1st October 2017) - Cao, Yupeng; Wang, Quansheng; Liu, Yanbo; Ning, Xianjin; Wang, Hao
Abstract: Ba(Mg1/3 Ta2/3 )O3 (BMT) powders were synthesized by the solid state reaction method. BMT thermal barrier coatings (TBCs) were deposited by atmospheric plasma spraying (APS). The phase composition and microstructure of the BMT coatings were characterized. The thermal cycling behavior of the BMT coatings was investigated by the water quenching method from 1150 °C to room temperature. The results reveal that BMT powders have an ordered hexagonal perovskite structure, whereas the as-sprayed coating of BMT has a disordered cubic perovskite structure because of the different degree of structural order for different treatment conditions. During thermal cycling testing, the entire spalling of coatings occurred within the BMT coating near the bond coat. This is attributed to the following reasons: (1) the growth of a thermally grown oxides (TGO) layer, which leads to additional stresses in the coatings; (2) the coefficient of thermal expansion mismatch between the BMT coating and bond coat, which develops enormous stress in the coatings; (3) the precipitation of Ba3 Ta5 O15 due to the evaporation of MgO during the spraying process, which changes the continuity of the coatings.